Thick electrode, preparation method thereof and lithium battery

By using a combination of composite adhesive and multi-component conductive agent in lithium batteries, the problems of thick electrode structure stability and cycle stability of lithium batteries are solved, and higher energy density and better cycle performance are achieved.

CN119581560AActive Publication Date: 2025-03-07EVE ENERGY CO LTD

Patent Information

Application Number
CN202411253126.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-03-07
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

While increasing the energy density of existing lithium batteries, it is difficult to achieve structural stability and cyclic stability of thick electrodes, and problems of pole sheet cracking and stratification are prone to occur.

Method used

A composite adhesive consisting of binder A and binder B is used, which includes sodium carboxymethylcellulose, polyacrylic binder and acrylonitrile polycopolymer, and binder B includes polytetrafluoroethylene and styrene butadiene rubber. The active slurry is prepared by dry or wet mixing method to improve the peeling force between the active coating and the current collector and the perfection of the conductive network.

Benefits of technology

The structural stability and cyclic stability of the thick electrode are achieved, the possibility of cracking and layering of the electrode sheet is reduced, and the energy density and fast charging performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a thick electrode and a preparation method thereof, and a lithium battery, the thick electrode comprises a current collector and an active coating, the active coating comprises an active material, a conductive agent, a dispersant and a composite binder, the composite binder comprises a binder A and a binder B, the binder A comprises at least two of sodium carboxymethyl cellulose, a polyacrylic acid binder and an acrylonitrile multipolymer, and the binder B comprises at least one of polytetrafluoroethylene and butadiene styrene rubber. The thick electrode has the characteristics of stable structure, good conductivity and high ion transmission efficiency, and the cycling stability of the battery using the thick electrode can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to a thick electrode and a preparation method thereof, and a lithium battery. Background Art

[0002] Lithium batteries have the advantages of high energy density, low cost, good safety performance, customizable appearance, and long cycle life. With these advantages, lithium batteries are now widely used in mobile electronic devices, energy storage, power vehicles, power tools and other fields. In the past five years, market demand has shown a steady growth trend, and as battery technology becomes more and more mature, its application scenarios will continue to expand in all aspects of life. Lithium batteries are mainly composed of positive electrode sheets, negative electrode sheets, diaphragms and electrolytes. The overall performance of the battery is closely related to each component. The electrode is an important component of the battery, and its structure has an important influence on the electrochemical performance and safety performance of the battery. The thick electrode structure increases the content of active materials per unit volume of the battery, reduces the amount of current collector used, and increases the energy density of the battery system without changing the battery chemical system. Therefore, improving the energy density of the battery through the design of thick electrode structure has received widespread attention.

[0003] Binder is an important component in the electrode. Its main function is to play a bonding role between the electrode active material, the conductive agent and the current collector, so that the electrode active materials have a certain porosity under the premise of mutual adhesion. At the same time, the active material is fixed on the current collector to prevent the active material particles from expanding and falling off during the charge and discharge process, and reduce the impedance between the current collector and the electrode material. PVDF is a commercial oily binder with NMP as the solvent, but NMP is expensive, not environmentally friendly and has a high recycling cost. Water-based binders have the same or even better performance as oily binders, and are safe, environmentally friendly and low-cost. Water-based binders have become a trend and hot spot in battery binder research. Currently, commonly used water-based binders include sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), acrylonitrile multipolymer (LA), etc. From the perspective of electrode processing performance and battery electrochemical performance, the performance requirements of the binder are very high. A single binder cannot meet all characteristics, so a composite binder composed of two binders is often used, such as CMC+SBR. Among them, it is difficult to achieve thick electrodes using the CMC+SBR system, as its coating surface density is low, and in the actual production process, the compaction density of the electrode coated using this system is low. Summary of the invention

[0004] The object of the present invention is to provide a thick electrode and a preparation method thereof, and a lithium battery. The thick electrode has the characteristics of stable structure, good conductivity, and high ion transmission efficiency, and can improve the cycle stability of the battery using the thick electrode.

[0005] According to one aspect of the present invention, a thick electrode is provided, comprising a current collector and an active coating, the active coating comprising an active material, a conductive agent, a dispersant and a composite binder, the composite binder comprising a binder A and a binder B, the binder A comprising at least two of sodium carboxymethyl cellulose, a polyacrylic acid binder and an acrylonitrile multipolymer, and the binder B comprising at least one of polytetrafluoroethylene and styrene-butadiene rubber.

[0006] By adopting a composite binder composed of at least three of binder A and binder B, not only can a stable bond between the active material and the binder be achieved, but it is also beneficial to improve the peeling force between the active coating and the current collector, thereby improving the structural stability of the thick electrode and reducing the possibility of cracking of the thick electrode. On the one hand, by selecting a composite binder, the binder forms multi-point contact on the surface of the active material, forming a three-dimensional cross-linked network, achieving three-dimensional bonding, effectively reducing the impedance between the active material, the conductive agent and the current collector, and improving the cycle stability of the battery using the thick electrode. On the other hand, compared with conventional binders, the use of the above-mentioned composite binder in this scheme is conducive to the uniform distribution of the conductive agent and the active material in the active coating, so that the inside of the thick electrode has a complete conductive network and bonding grid. Secondly, the use of the above-mentioned composite binder is conducive to the preparation of thick electrodes with a thickness greater than that of commercially available pole pieces, thereby improving the energy density of the battery.

[0007] Preferably, the molecular weight of sodium carboxymethyl cellulose is ≥10,000 Dalton, the molecular weight of the polyacrylic acid binder is ≥10,000 Dalton, the molecular weight of the acrylonitrile multipolymer is ≥10,000 Dalton, the molecular weight of polytetrafluoroethylene is ≥10,000 Dalton, and the molecular weight of styrene-butadiene rubber is ≥10,000 Dalton.

[0008] Preferably, binder A includes sodium carboxymethyl cellulose and acrylonitrile multipolymer, and binder B includes polytetrafluoroethylene. Sodium carboxymethyl cellulose CMC, acrylonitrile multipolymer LA and polytetrafluoroethylene PTFE can form a three-dimensional cross-linked network, improve the interfacial bonding force between the conductive agent and the active material, increase the stress node of the thick electrode, help maintain the stability of the electrode structure, reduce the shedding of active materials during the cycle, and thus improve the cycle life of the battery. At the same time, the use of the above-mentioned composite binder to prepare thick electrodes can also improve the peeling force between the active coating and the current collector, improve the structural stability of the thick electrode, effectively reduce the cracking and stratification of the pole piece, and improve the structural stability of the thick electrode during the battery cycle.

[0009] Preferably, the mass ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene is 0.1-0.5: 0.3-0.7: 3.0-5.0. By regulating the ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene, it is possible to not only improve the bonding effect of the composite binder and the structural stability of the thick electrode, but also to make the thick electrode have a suitable porosity and tortuosity, which is conducive to the penetration of the electrolyte, effectively improve the electronic conductivity and ionic conductivity of the thick electrode, and improve the fast charging performance and cycle capacity retention rate of the battery using the thick electrode.

[0010] Preferably, the conductive agent includes carbon black, carbon nanotubes and graphene. The use of the above-mentioned ternary conductive agent including carbon black, carbon nanotubes and graphene in combination with a composite binder is conducive to the strong bonding between the conductive agent and the active material, forming a large number of conductive contact sites and efficiently constructing a conductive path, thereby reducing the transmission resistance of lithium ions inside the thick electrode and improving the battery charging and discharging efficiency and cycle performance. The use of the above-mentioned ternary conductive agent can make the contact mode between the conductive agent and the active material a mixed contact mode of "point-line-surface", forming a three-dimensional conductive network with efficient transmission, which helps to improve the effective diffusion coefficient of the active material and the degree of electrolyte infiltration, so that more active materials participate in the electrochemical reaction and improve the energy density of the battery.

[0011] Preferably, the mass ratio of carbon black, carbon nanotubes and graphene is 0.3-0.6: 0.7-1.2: 1.0-1.5. By adjusting the mass ratio of carbon black, carbon nanotubes and graphene within the above range, the conductive network of the thick electrode can be optimized, the high-quality transmission path of lithium ions through the electrode can be promoted to effectively pass through, polarization can be reduced and the kinetic performance can be improved. Among them, carbon black and active materials are in point-to-point contact. When used alone, a higher amount of addition is required to improve the chemical properties of the battery, which is not conducive to improving the energy density of the battery; carbon nanotubes and active materials are in point-to-line contact, which makes it easier to form a conductive network, but they have a high aspect ratio, a large specific surface area, and a high specific surface energy. They are easy to cross-entangle with each other, and they are easy to agglomerate during actual use, resulting in poor local transmission paths; graphene and active materials are in point-to-surface contact, which can provide a large number of conductive contact sites, but the cost is high.

[0012] Preferably, the dispersant includes at least one of polyacrylic acid and sodium carboxymethyl cellulose dispersants, and the molecular weight of the dispersant is less than 10,000 Daltons. The dispersant with a molecular weight less than 10,000 Daltons contains both hydrophilic and hydrophobic groups, so that the viscosity of the active slurry containing the active material is less than 1000 mPa·s, which is conducive to preparing an active slurry with an overestimated content and low viscosity, and achieves dispersion and stabilization of the active slurry through the double electric layer effect combined with the steric hindrance theory.

[0013] According to another aspect of the present invention, a method for preparing the above-mentioned thick electrode is provided, including a slurrying operation for preparing an active slurry, and the slurrying operation adopts a dry mixing method or a wet mixing method; the dry mixing method includes the following operations: firstly, the active material, the binder A and a part of the conductive agent are dry-mixed to obtain a first mixed dry material, and then the first mixed dry material is mixed with a solvent to obtain a second mixed slurry with a solid content of 81 to 85%, and then the second mixed slurry is mixed with a dispersant, a solvent, a binder B and the remaining conductive agent to obtain an active slurry; the wet mixing method includes the following operations: firstly, the binder A and the solvent are mixed to obtain a mixed slurry A with a solid content of 1 to 5%, and then the mixed slurry A is mixed with a dispersant, a conductive agent, an active material, the remaining solvent and a binder B to obtain an active slurry.

[0014] As the thickness of the electrode increases, the coating process becomes more difficult to implement, and cracking and delamination are prone to occur during the coating and drying of the pole piece. By adopting the above-mentioned pulping process, a slurry with appropriate viscosity and high solid content can be prepared to increase the uniformity, leveling and stability of the slurry, reduce the solvent content, and increase the solvent evaporation rate during the coating process, which is conducive to slowing down the coating cracking phenomenon and ensuring the drying effect of the pole piece. The use of the above-mentioned composite binder is conducive to regulating the viscosity of the active slurry that forms the active coating, improving the stability of the active slurry, and reducing the probability of cracking and delamination of the pole piece caused by the excessive thickness of the electrode. At the same time, by adopting a dry mixing method or a wet mixing method for pulping, and accurately controlling the solid content during the pulping process, an active slurry with a solid content of 60-72% and a slurry viscosity of 4000-9000mPa·s can be prepared. This can not only increase the floating resistance of the binder, inhibit the floating of the binder, and help improve the bonding strength between the material area and the current collector, but also reduce the solvent, thereby reducing the possibility of the binder migrating upward with the solvent. The active slurry not only has good fluidity but also has a high slurry solid content. After a 48-hour slurry stability test at room temperature, the viscosity and solid content of the active slurry remain almost unchanged, showing excellent stability. This not only ensures the performance of the slurry during long-term storage and transportation, but also provides a stable foundation for subsequent coating and drying processes. The high-solid content slurry significantly improves the dispersion uniformity, enhances the stability of the slurry and the coating and drying efficiency, and effectively slows down the cracking phenomenon, providing a strong guarantee for product quality control and production efficiency improvement.

[0015] Preferably, when the pulping operation adopts the dry mixing method, the specific operation of mixing the second mixed slurry with the dispersant, the solvent, the binder B and the remaining conductive agent includes: first mixing the second mixed slurry with the dispersant and part of the solvent to obtain a third mixed slurry with a solid content of 77 to 80%; then mixing the remaining conductive agent with the third mixed slurry to obtain a fourth mixed slurry with a solid content of 73 to 75%; then mixing the fourth mixed slurry with the binder B to obtain an active slurry with a solid content of 60 to 72%.

[0016] Preferably, when the slurry making operation adopts the wet mixing method, the specific operation of mixing the mixed slurry A with the dispersant, the conductive agent, the active material, the remaining solvent and the binder B includes: first mixing the mixed slurry A with the dispersant and the conductive agent to obtain the mixed slurry B, then mixing the active material with the mixed slurry B in batches, and then adding the solvent and the binder B to the mixed slurry B, mixing, and obtaining an active slurry with a solid content of 60 to 72%.

[0017] Preferably, when the pulping operation adopts a wet mixing method, in the process of mixing the active material with the mixed slurry B in batches, the mass of the active material mixed for the first time does not exceed 50% of the active material.

[0018] Preferably, the solid content of the active slurry is 60-72%.

[0019] Preferably, in the pulping operation, binder A, dispersant and binder B are added to the slurry system in sequence.

[0020] Preferably, after the slurrying operation is completed, a coating operation is also included, and the coating operation includes: coating the active slurry on the surface of the current collector at a coating speed of 3 to 10 m / min, and the single-side coating surface density is not higher than 700 g / m 2 , then dry the active slurry at a temperature of 80 to 120°C and a wind frequency of 10 to 35 Hz to obtain a thick electrode. In the conventional coating operation for preparing thick electrodes, when the electrode thickness is too large, the moisture content is high, the evaporation removal path is long, the evaporation time is long, the pole piece is in the oven environment for a long time, the migration of the binder to the surface is aggravated, and cracks and a decrease in the pole piece peeling force are very likely to occur, affecting the pole piece processing performance and battery electrochemical performance. In addition, the distribution of active materials, conductive agents, etc. is uneven, resulting in an imperfect conductive network inside the electrode, which leads to increased impedance. By adjusting the slurry process to make the active slurry have a high solid content and fluidity, and further adjusting the coating process, on the one hand, it can slow down the phenomenon of the decrease in peeling force caused by the upward migration of the binder accompanying the solvent during the coating process, and on the other hand, the use of an adapted temperature and wind frequency can reduce the difference in the evaporation rate of the solvent at each position of the active slurry during the drying process of the pole piece, and slow down the cracking of the pole piece surface or lower layer.

[0021] According to another aspect of the present invention, a lithium battery is provided, comprising an electrode and an electrolyte, wherein the electrode comprises the thick electrode. The lithium battery uses the thick electrode, which can improve the battery energy storage capacity, the battery structural stability and the cycle stability, and is conducive to extending the service life of the lithium battery.

[0022] Preferably, the thickness of the thick electrode is 160-400 μm. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0024] Example 1

[0025] The present embodiment provides a thick electrode, including a current collector and an active coating, wherein the active coating includes an active material, a conductive agent, a dispersant, and a composite binder, wherein the active material is manganese dioxide, and the conductive agent is a composite conductive agent composed of carbon black, carbon nanotubes, and graphene in a mass ratio of 0.5:1:1.2. The dispersant is polyacrylic acid with a molecular weight of <10,000 Daltons. The composite binder includes a binder A and a binder B, wherein the binder A is sodium carboxymethyl cellulose (CMC) with a molecular weight of ≥10,000 Daltons and an acrylonitrile multipolymer (LA) with a molecular weight of ≥10,000 Daltons, and the binder B is polytetrafluoroethylene (PTFE) with a molecular weight of ≥10,000 Daltons, and the mass ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer, and polytetrafluoroethylene is 0.5:0.5:5.0.

[0026] The method for preparing thick electrodes comprises the following operations:

[0027] (1) Pulping operation:

[0028] The active slurry includes active material, composite binder, composite conductive agent, dispersant and solvent in a mass ratio of 94:4:2:0.5.

[0029] Step 1, dry-mixing the active material, the binder A, and the carbon black conductive agent, stirring and dispersing to obtain a first mixed dry material;

[0030] Step 2: Mix the first mixed dry material with the solvent, stir and disperse, and obtain a second mixed slurry with a solid content of 83%.

[0031] Step 3: Add a dispersant and an appropriate amount of solvent to the second mixed slurry, and stir and disperse the mixture in a vacuum state to obtain a third mixed slurry with a solid content of 78%.

[0032] Step 4: Mix the remaining conductive agent with the third mixed slurry, and stir and disperse them in a vacuum state to obtain a fourth mixed slurry with a solid content of 74%.

[0033] Step 5: Mix the binder B with the fourth mixed slurry, stir and disperse them in a vacuum state, and sieve them to obtain an active slurry with a solid content of 70.5% and a viscosity of 8256 mPa·s.

[0034] (2) Coating operation:

[0035] The active slurry prepared by the slurrying operation is coated on the surface of the current collector at a coating speed of 4.6 m / min, and the single-sided coating surface density is 400 g / m 2 Then, the active slurry was dried at a temperature of 110°C and a wind frequency of 11 Hz to obtain a thick electrode with a thickness of 300 μm.

[0036] In other embodiments, the type and amount of active materials and dispersants can be adjusted according to actual conditions; the solid contents of the second mixed slurry, the third mixed slurry, and the fourth mixed slurry in the slurrying operation can be adjusted; or the coating speed, single-sided coating surface density, drying temperature, wind frequency, and thickness of thick electrodes in the coating operation can be adjusted; or additives can be introduced into the active coating according to actual applications.

[0037] Example 2

[0038] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that an equal mass of styrene-butadiene rubber is used to replace the binder B in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0039] Example 3

[0040] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that equal masses of sodium carboxymethyl cellulose, polyacrylic acid binder and acrylonitrile multipolymer are used to replace the binder A in Example 1, and the mass ratio of sodium carboxymethyl cellulose, polyacrylic acid binder and acrylonitrile multipolymer is 0.5:0.3:0.5. The remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0041] Example 4

[0042] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that the mass ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene is adjusted to 0.1:0.1:3.0, and the other raw material ratios and preparation methods are strictly consistent with Example 1.

[0043] Example 5

[0044] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that the mass ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene is adjusted to 0.5:0.8:5.0, and the other raw material ratios and preparation methods are strictly consistent with Example 1.

[0045] Example 6

[0046] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that an equal mass of carbon black is used to replace the carbon nanotubes and graphene in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0047] Example 7

[0048] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that an equal mass of carbon black is used to replace the graphene in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0049] Example 8

[0050] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that in step 2 of the slurrying operation, the solid content of the prepared second mixed slurry is 90%, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0051] Example 9

[0052] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that: in the slurrying operation, the order of adding the dispersant is adjusted so that the dispersant is added after the binder B is mixed with the fourth mixed slurry. The specific operation is: omitting step 3, and adding the dispersant to the slurry system after the binder B is mixed with the fourth mixed slurry. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.

[0053] Example 10

[0054] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that in the slurrying operation, the order of adding the dispersant is adjusted so that the dispersant is added to the slurry system before the binder A. The specific operation is: adding the dispersant in step 1 and omitting the addition of the dispersant in step 3, and adding the binder A in step 3 and omitting the addition of the binder A in step 1. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0055] Embodiment 11

[0056] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that: in the slurrying operation, the order of adding the dispersant and the binder B is adjusted so that the binder A, the binder B, and the dispersant are added to the slurry system at the same time. The specific operation is: adding the dispersant and the binder B in step 1, while omitting the addition of the dispersant in step 3, and omitting the addition of the binder B in step 5. The rest of the raw material ratios and the preparation method are strictly consistent with those in Example 1.

[0057] Example 12

[0058] This embodiment refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this embodiment and Example 1 is that in the pulping operation, a wet mixing method is adopted, and the other raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0059] Specific pulping operations include:

[0060] Step 1: Mix the binder A and the solvent, stir and disperse them under vacuum to obtain a mixed slurry A with a solid content of 1 to 5% and a viscosity in the range of 2000 to 6000 mPa·s.

[0061] Step 2: Mix the dispersant with the mixed slurry A, and stir and disperse them under vacuum to obtain a mixed slurry B;

[0062] Step 3, mixing the carbon black conductive agent with the mixed slurry B, stirring and dispersing them under a vacuum state to obtain a mixed slurry C;

[0063] Step 4: Mix the remaining conductive agent with the mixed slurry C, stir and disperse them under vacuum to obtain a mixed slurry D;

[0064] Step 5: Mix 50 wt% of active material with mixed slurry D, stir and disperse under vacuum to obtain mixed slurry E; wherein 50 wt% of active material means that the mass of the active material input is 50% of the mass of all active materials in the thick electrode.

[0065] Step 6: adding the remaining active materials to the mixed slurry E, stirring and dispersing, to obtain a mixed slurry F;

[0066] Step 7: Add binder B and the solution to the mixed slurry F, stir, disperse and sieve under vacuum to obtain an active slurry with a solid content of 70.5%.

[0067] In other embodiments, the type and amount of active materials and dispersants can be adjusted according to actual conditions; the solid content or viscosity of mixed slurry A, mixed slurry B, mixed slurry C, mixed slurry D, mixed slurry E, and mixed slurry F in the slurrying operation can be adjusted; or the coating speed, single-sided coating surface density, drying temperature, wind frequency, thickness of thick electrodes, etc. in the coating operation can be adjusted.

[0068] Embodiment 13

[0069] This embodiment refers to the preparation method provided in Example 12 to prepare a thick electrode. The difference between this embodiment and Example 12 is that in step 1 of the slurrying operation, the solid content of the prepared mixed slurry A is 10%, and the remaining raw material ratios and preparation methods are strictly consistent with Example 12.

[0070] Embodiment 14

[0071] This embodiment refers to the preparation method provided in Example 12 to prepare a thick electrode. The difference between this embodiment and Example 12 is that in the coating operation, the active slurry prepared by the slurrying operation is coated on the surface of the current collector at a coating speed of 12 m / min, and the single-sided coating surface density is 400 g / m 2 Then, the active slurry was dried at 80°C and 35 Hz wind frequency to obtain a thick electrode.

[0072] Comparative Example 1

[0073] This comparative example refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this comparative example and Example 1 is that an equal mass of sodium carboxymethyl cellulose is used to replace the binder A in Example 1, and an equal mass of styrene-butadiene rubber is used to replace the binder B in Example 1, that is, the composite binder includes sodium carboxymethyl cellulose and styrene-butadiene rubber, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0074] Comparative Example 2

[0075] This comparative example refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this comparative example and Example 1 is that an equal mass of sodium carboxymethyl cellulose is used to replace the binder A in Example 1, that is, the composite binder includes sodium carboxymethyl cellulose and polytetrafluoroethylene, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1.

[0076] Comparative Example 3

[0077] This comparative example refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this comparative example and Example 1 is that an equal mass of polyacrylic acid binder is used to replace the binder B in Example 1, that is, the composite binder includes sodium carboxymethyl cellulose, polyacrylic acid binder and acrylonitrile multipolymer, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1.

[0078] Comparative Example 4

[0079] This comparative example refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this comparative example and Example 1 is that the composite binder includes sodium carboxymethyl cellulose and acrylonitrile multipolymer, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1, especially the mass ratio of sodium carboxymethyl cellulose and acrylonitrile multipolymer is consistent with the mass ratio of sodium carboxymethyl cellulose and acrylonitrile multipolymer in Example 1.

[0080] Comparative Example 5

[0081] This comparative example refers to the preparation method provided in Example 1 to prepare a thick electrode. The difference between this comparative example and Example 1 is that an equal mass of polytetrafluoroethylene is used to replace the composite binder in Example 1, that is, the composite binder only includes polytetrafluoroethylene, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.

[0082] Test Case

[0083] Test objects: thick electrodes provided in Examples 1 to 14 and Comparative Examples 1 to 5.

[0084] Test items and test methods:

[0085] (1) Diaphragm resistance: The ACCFILM diaphragm resistance tester is used. The instrument uses a controllable voltage dual-probe resistor to directly test the thick electrode as the test object, and the output measurement value is the diaphragm resistance.

[0086] (2) Electrode peeling force test: The thick electrodes provided by the above test subjects were cut into a size of 24 mm in width and 150 mm in length, and then tested in a tensile testing machine with a tensile angle of 180°, and the electrode peeling force was recorded.

[0087] (3) Flexibility test: The test object was subjected to a flexibility test on a TX116 toughness tester. The diameter of the shaft rod was 2 mm. The surface of the thick electrode after winding was observed to see if there were any cracks.

[0088] Test results: as shown in Table 1.

[0089] Table 1. Performance results of each test object

[0090]

[0091]

[0092] Result analysis:

[0093] By comparing the test performance of Examples 1 to 14 with Comparative Examples 1 to 5 in Table 1, it can be found that compared with the thick electrodes provided in Comparative Examples 1 to 5, the thick electrodes provided in Examples 1 to 14 have the characteristics of high peeling force and low film resistance, that is, the thick electrodes provided in Examples 1 to 14 have stable structures, good conductivity, and high ion transmission efficiency. Among them, the electrode peeling force of the thick electrodes provided in Examples 1 to 14 is not less than 0.25N, and the film resistance is not higher than 162.3mΩ.

[0094] By comparing the types of binders used in Examples 1 to 2 with those in Comparative Examples 1 to 5, it can be seen that the composite binder used in the thick electrodes provided in Comparative Examples 1 to 2 is a binary binder, which is composed of binder A and binder B, and binder A is only a single binder; the composite binder used in the thick electrode provided in Comparative Example 3 is a ternary binder and only binder A is used; the composite binder used in the thick electrode provided in Comparative Example 4 is a binary binder and only binder A is used; the binder used in the thick electrode provided in Comparative Example 5 is only polytetrafluoroethylene in binder B; the composite binder used in the thick electrodes provided in Examples 1 to 2 is a ternary binder, which is composed of at least two binders A and a single binder B. By comparing the performances of the thick electrodes provided in Examples 1 to 2 and Comparative Examples 1 to 5 in Table 1, it can be found that the electrode peeling force of the thick electrodes provided in Examples 1 to 2 is higher than that of the thick electrodes provided in Comparative Examples 1 to 5. This shows that in the process of preparing the thick electrode, a composite binder including binder A and binder B is used, and binder A includes at least two of sodium carboxymethyl cellulose, polyacrylic acid binder, and acrylonitrile multipolymer, and binder B includes at least one of polytetrafluoroethylene and styrene-butadiene rubber. This can not only achieve a stable bond between the active material and the binder, but also help to improve the peeling force between the active coating and the current collector, thereby improving the structural stability of the thick electrode.

[0095] Among them, the comprehensive performance of Example 1 is compared with that of Comparative Examples 4 to 5. The thick electrode provided by Comparative Example 4 using sodium carboxymethyl cellulose and acrylonitrile multipolymer as the composite binder has a diaphragm resistance of 110.5 mΩ and a pole piece peeling force of only 0.10 N; the thick electrode provided by Comparative Example 5 using polytetrafluoroethylene as the binder has a diaphragm resistance of 103.6 mΩ and a pole piece peeling force of only 0.08 N; but the diaphragm resistance of the thick electrode provided by Example 1 using sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene as the composite binder is lower than the diaphragm resistance of the thick electrode provided by Comparative Example 4 or Comparative Example 5, and the pole piece peeling force of the thick electrode provided by Example 1 is also higher than the pole piece peeling force of the thick electrode provided by Comparative Example 4 or Comparative Example 5. This shows that there is a synergistic relationship between sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene, so that the thick electrode made by using the composite binder has a large pole piece peeling force, ensuring the close bonding between the active coating and the current collector, while effectively reducing the membrane resistance of the thick electrode, promoting the efficient transmission of charge, thereby improving the overall performance and stability of the battery. Comparing the appearance of the thick electrode provided in Example 1 with that provided in Example 2, it can be found that the thick electrode provided in Example 1 has no cracks on the pole piece after winding, while the thick electrode provided in Example 2 has local cracks on the pole piece surface after winding, which shows that compared with the thick electrode using sodium carboxymethyl cellulose, acrylonitrile multipolymer and styrene-butadiene rubber in Example 2, the use of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene in Example 1 can increase the stress nodes of the thick electrode, help maintain the stability of the electrode structure, can effectively reduce the cracking and delamination of the pole piece, and improve the structural stability of the thick electrode during the battery cycle.

[0096] By comparing the test performances of Example 1 and Examples 3 to 4 in Table 1, it can be found that the comprehensive performance of the thick electrode provided by Example 1 is better than that of the thick electrodes provided by Examples 3 to 4, which shows that when the mass ratio of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polytetrafluoroethylene is 0.1 to 0.5: 0.3 to 0.7: 3.0 to 5.0, the bonding effect of the composite binder is better, the pole piece peeling force of the thick electrode is greater, and the membrane resistance is smaller.

[0097] By comparing the test performances of Example 1 and Examples 6 to 7 in Table 1, it can be found that the film resistance of the thick electrode provided by Example 1 is smaller than that of the thick electrodes provided by Examples 3 to 4. This shows that when a ternary conductive agent composed of carbon black, carbon nanotubes and graphene is used, a three-dimensional conductive network can be formed in the active coating, thereby reducing the transmission resistance of lithium ions inside the thick electrode.

[0098] Comparing the test performance of Example 1 with that of Example 8 in Table 1, it can be found that, compared with Example 8, in the pulping operation, the thick electrode provided by Example 1 in which the solid content of the second mixed slurry is controlled at 81-85% has higher electrode peeling force and lower film resistance. Comparing the test performance of Example 1 with that of Examples 9-11 in Table 1, it can be found that by adjusting the order of adding the dispersant, so that the binder A, the dispersant, and the binder B are added to the slurry system in sequence, it is beneficial to prepare an active slurry with high solid content and moderate viscosity, which is beneficial to enhance the stability of the slurry and the coating and drying efficiency, effectively slowing down the cracking phenomenon, and providing a strong guarantee for product quality control and production efficiency improvement.

[0099] Comparing the thick electrodes provided by Example 1 with those provided by Examples 12 to 13, it can be found that the thick electrode obtained by Example 1 using the dry mixing method has a greater electrode peeling force and a smaller membrane resistance than that obtained by Examples 12 to 13 using the wet mixing method. Comparing the thick electrodes provided by Example 1 with those provided by Example 14, it can be found that Example 14 cannot achieve complete drying using the same drying time as Example 1, so Example 14 tests the membrane resistance and electrode peeling force after a long period of drying. During the coating operation, if the coating speed is too fast, it is easy to make the electrode difficult to dry, and if the coating speed is too slow, it is easy to cause the electrode to crack, so when the coating speed is 3 to 10 m / min, it is easy to obtain a thick electrode with a good appearance.

[0100] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A thick electrode, characterized in that: It includes a current collector and an active coating, wherein the active coating includes an active material, a conductive agent, a dispersant and a composite binder, wherein the composite binder includes a binder A and a binder B, wherein the binder A includes at least two of sodium carboxymethyl cellulose, a polyacrylic acid binder and an acrylonitrile multipolymer, and the binder B includes at least one of polytetrafluoroethylene and styrene-butadiene rubber.

2. The thick electrode according to claim 1, characterized in that The binder A includes the sodium carboxymethyl cellulose and the acrylonitrile multipolymer, and the binder B includes the polytetrafluoroethylene.

3. The thick electrode according to claim 2, characterized in that: The mass ratio of the sodium carboxymethyl cellulose, the acrylonitrile multi-polymer and the polytetrafluoroethylene is 0.1-0.5: 0.3-0.7: 3.0-5.

0.

4. The thick electrode according to claim 1, characterized in that: The conductive agent includes carbon black, carbon nanotube and graphene.

5. The thick electrode according to claim 4, characterized in that: The mass ratio of the carbon black, the carbon nanotube and the graphene is 0.3-0.6:0.7-1.2:1.0-1.

5.

6. The thick electrode according to claim 1, characterized in that: The dispersant includes at least one of polyacrylic acid and sodium carboxymethyl cellulose dispersants, and the molecular weight of the dispersant is less than 10,000 Daltons.

7. A method for preparing a thick electrode as claimed in any one of claims 1 to 6, characterized in that: The invention comprises a pulping operation for preparing an active slurry, wherein the pulping operation adopts a dry mixing method or a wet mixing method; The dry mixing method includes the following operations: firstly dry mixing the active material, the binder A and part of the conductive agent to obtain a first mixed dry material, then mixing the first mixed dry material with a solvent to obtain a second mixed slurry with a solid content of 81-85%, and then mixing the second mixed slurry with a dispersant, a solvent, the binder B and the remaining conductive agent to obtain the active slurry; The wet mixing method includes the following operations: firstly mixing the binder A and the solvent to obtain a mixed slurry A with a solid content of 1 to 5%, and then mixing the mixed slurry A with a dispersant, the conductive agent, the active material, the remaining solvent and the binder B to obtain the active slurry.

8. The method according to claim 7, characterized in that: After the slurrying operation is completed, a coating operation is also included, and the coating operation includes: coating the active slurry on the surface of the current collector at a coating speed of 3 to 10 m / min, and the single-side coating surface density is not higher than 700 g / m 2 Then, the active slurry is dried at a temperature of 80 to 120° C. and a wind frequency of 10 to 35 Hz to obtain the thick electrode.

9. A lithium battery, characterized in that: The invention comprises an electrode and an electrolyte, wherein the electrode comprises the thick electrode as claimed in any one of claims 1 to 6.

10. The lithium battery according to claim 9, characterized in that: The thickness of the thick electrode is 160-400 μm.

Citation Information

Patent Citations

  • Battery cathode slurry and preparation method of battery cathode slurry

    CN103794798A

  • High-specific-capacity silicon-based negative electrode composite binder and preparation method for negative plate containing same

    CN106058259A

  • Composite binder for lithium battery and application of composite binder

    CN106602073A

  • Low-temperature-resistant lithium-ion battery long in service life

    CN107093718A

  • Proportioning process for graphite negative electrode of lithium ion battery

    CN107706348A

Cited By

  • Organic-inorganic compound thick electrode and preparation method and application thereof

    CN121601578A

  • An organic-inorganic compound thick electrode, a preparation method and application thereof

    CN121601578B

  • Preparation method and application of ultra-high surface load organic electrode

    CN121662746A

  • Preparation method and application of an organic electrode with ultra-high areal loading

    CN121662746B